PROFESSIONALISMIN JUVENILE CORRECTIONS: FAIRNESS AND BUREAUCRATIC LEGITIMACY - Hassan, Nazirah (International Journal of Psychosocial Rehabilitation, 2020)
All individuals incarcerated in correctional facilities are entitled to humane and fair treatment. This study seeks to explain levels of professionalism in juvenile justice institutions. It further investigates how this dimension has an influence on aggressive behaviour among young offenders in the institutions. The study comprised a survey completed by 289 male and female young offenders, aged 12 to 21 years old, in 8 juvenile justice institutions in Malaysia. The professionalism subscale of the Measuring Quality of Prison Life (MQPL)and the scale version of Direct and Indirect Prisoner behaviour Checklist (DIPC-SCALEDr) were used in the study. The findings demonstrate that majority of young offenders reported moderate levels of four professionalism dimensions in the institutions. Furthermore, two dimensions of professionalism i.e. fairness and bureaucratic legitimacy are reported to significantly influence aggressive behaviour among young offenders. This study suggests that young offenders will be more likely to comply with authority’s decision and regulations when they are treated with fairness and respectful relationships. As the heart of correctional quality, staff play an important role tocreate positive correctional environment and to improve the quality of life among young offenders in the institutions.